Financial Resilience amid Covid-19 Pandemic: Lesson from Locals in the Southern Beach of West Java - Agung W. HANDARU; Usep SUHUD; Saparuddin MUKHTAR (Communications of International Proceedings, 2021)
Almost all tourism activities on the south coast of West Java Province have stopped due to the Covid-19 pandemic. The cessation of tourism activities in this area has lowered the economy of most villagers. People who usually earn additional income from the tourism sector now have to find ways to provide for their families. To survive during this pandemic, locals in Mekarlaksana village successfully set up a new business to process peanuts into cooking oil. Villagers determinedly managed vacant land near the village to be used as peanut farming. From processing peanuts into cooking oil, the villagers succeeded in getting additional income from selling this oil to the nearest city. The people of the Saganten Village also carried out another effort to survive the pandemic. Villagers succeeded in establishing a bamboo-based business into a multi-purpose basket product. This basket product was successfully sold to cities near the village and generated financial benefits for the villagers. Although the production volume in the two towns is still limited and uses low technology, this business can help the economy of residents who have lost their income due to the cessation of tourism activities. To improve the villagers' economy, the government and investors can provide additional capital and technology investment to enlarge the business scale.
Keywords: Financial Resilience; Small Enterprise; Poverty Alleviation